Assessing the Accuracy of Google Maps in Rural Areas - Tolibjon o‘g‘li, Murodilov Khasanboy; Ikrimjon o‘g‘li, Muminov Islombek; Rasuljon o‘g‘li, Abdumalikov Ravshanbek (European Journal of Life Safety and Stability (2660-9630), 2023)
Google Maps has become an important tool for navigation and location-based services. However, the accuracy of Google Maps in rural areas has been a topic of debate. This article aims to assess the accuracy of Google Maps in rural areas using various methods, including field testing and comparison with other mapping services. The results show that while Google Maps is generally accurate in rural areas, there are still some discrepancies that need to be addressed.